Called to preach : fulfilling the high calling of expository preaching - Lawson, Steven J. (Baker Books, 2022)
"With insights from Scripture and examples from church history, this practical guide offers aspiring preachers the tools they need to discern whether they are being called to expository preaching"--
Includes bibliographical references (pages 199-203).
Keywords: Expository preaching